A new type of catheter for the artifical insenmination in cows - ΚΟΥΤΣΟΥΡΗΣ, XP. Δ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The function, application and the advantages of a new type of a catheter for artificial insemination in the cow with frozen semen packed in plastic straws are described